2007
DOI: 10.1109/lgrs.2006.890540
|View full text |Cite
|
Sign up to set email alerts
|

Classification and Extraction of Spatial Features in Urban Areas Using High-Resolution Multispectral Imagery

Abstract: Abstract-Classification and extraction of spatial features are investigated in urban areas from high spatial resolution multispectral imagery. The proposed approach consists of three steps. First, as an extension of our previous work [pixel shape index (PSI)], a structural feature set (SFS) is proposed to extract the statistical features of the direction-lines histogram. Second, some methods of dimension reduction, including independent component analysis, decision boundary feature extraction, and the similari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 162 publications
(69 citation statements)
references
References 12 publications
1
65
0
3
Order By: Relevance
“…This suggests that when using GE imagery for land use/cover mapping, more attention should be given to its spatial characteristics (such as shape, texture and context of objects) in the classification algorithm as these are well described in GE imagery. This conclusion agrees well with the study by Huang et al, which showed that the QB classification based on spatial features (i.e., shape index, length-width ratio) is significantly better than that based on spectral bands [45].…”
Section: Potentials Analysis Of Ge Imagery For Land Use/cover Mappingsupporting
confidence: 92%
“…This suggests that when using GE imagery for land use/cover mapping, more attention should be given to its spatial characteristics (such as shape, texture and context of objects) in the classification algorithm as these are well described in GE imagery. This conclusion agrees well with the study by Huang et al, which showed that the QB classification based on spatial features (i.e., shape index, length-width ratio) is significantly better than that based on spectral bands [45].…”
Section: Potentials Analysis Of Ge Imagery For Land Use/cover Mappingsupporting
confidence: 92%
“…Various spectral-spatial classification methods have been proposed to extract urban land use maps. One popular method is to add into the original remote sensing spectral bands textural information derived from the original RSI, e.g., a grayscale co-occurrence matrix [13,14], morphological features [15], and a pixel shape index [16]. For example, Li et al used a Bayesian network to categorize building objects into different land use types based on their morphological, geometric, and contextual attributes [17].…”
Section: Introductionmentioning
confidence: 99%
“…[2] The tentative results of simulated and genuine datasets, demonstrate that the proposed methodology can effectively lessen the pseudo edges of the total variation regularization in the flat areas, and keep up the partial smoothness of the HR images. [6] More significantly with the comparison of the usual pixel based spatial data adaptive method, the method based on proposed region can do better i.e., in the super resolution process it helps in avoiding the effect of noise and maintains the robustness with changes in the intensity of noise.…”
Section: Proposed Methodsmentioning
confidence: 87%